City power urban governance in a global age - Schragger, Richard C. 1970- (Oxford University Press, 2016)
"Reigning theories of urban power suggest that in a world dominated by footloose transnational capital, cities have little capacity to effect social change. In City Power, Schragger challenges this conventional wisdom, arguing that cities can and should pursue aims other than making themselves attractive to global capital. Using the municipal living wage movement as an example, Schragger explains why cities are well-positioned to address issues like income equality and how our institutions can be designed to allow them to do so"...